The Cost of EU Trade Protection in Textiles and Clothing - Dean Spinanger; Joseph F. Francois; Hans H. Glismann (Kiel Institute of World Economics (IfW), 2000)
This paper estimates the costs of EU restraints on trade in textiles and clothing. After explaining the methods used, we examine the impact of an opening up of EU trade in textiles and clothing, inter alia to those economies where the textile and clothing (T&C) industries command sizeable shares of exports and output. The estimates are based, firstly, on a partial equilibrium analysis allowing us to directly cover the effects of liberalization on the importation, production and consumption of T&C products; secondly, a general equilibrium analysis incorporates the wide-sweeping indirect costs of ATC within the EU. It turns out that in 1997 EU consumers paid roughly ECU 25 billion more for T&C products, due to quotas, tariffs and indirect effects.
Keywords: F13; F14; L67; 330; Agreement on Textiles and Clothing - ATC; Multi-fiber Arrangement; Costs of Protection; EU trade policy; Textil- und Bekleidungsindustrie; Protektionismus; Soziale Kosten; Wohlfahrtseffekt; Welttextilabkommen; Außenhandelsliberalisierung; Wirtschaftspolitische Wirkungsanalyse; Allgemeines Gleichgewicht; Schätzung; EU-Staaten